一种纳米酶及其制备方法与应用 (2023)
本发明公开了一种纳米酶及其制备方法与应用，其中，所述纳米酶包括铑纳米颗粒和结合在所述铑纳米颗粒表面的丝氨酸。本发明提供的纳米酶(Rh-Ser)具有超小的尺寸，低于肾小管滤过阈值；同时由于丝氨酸具有靶向受损肾小管表达的肾损伤分子-1(KIM-1)的能力，因此丝氨酸的修饰可以使得铑纳米颗粒具备一定的肾靶向能力，使得铑纳米颗粒能够有效的富集于受损小鼠肾脏，清除肾小管内大量的活性氧或活性氮以缓解和治疗甘油诱导的急性肾损伤，并且具有优异的抗炎能力。另外，这些Rh-Ser具有良好的治疗效果，同时具有优异的生物相容性和生物安全性。 The invention discloses a nano-enzyme as well as a preparation method and application thereof, and the nano-enzyme comprises rhodium nano-particles and serine combined on the surfaces of the rhodium nano-particles. The nano-enzyme (Rh-Ser) provided by the invention has an ultra-small size which is lower than a renal tubule filtration threshold value; meanwhile, due to the fact that serine has the capacity of targeting renal injury molecularly 1 (KIM-1) expressed by damaged renal tubules, modification of serine can enable the rhodium nano-particles to have certain renal targeting capacity, and the rhodium nano-particles can be effectively enriched in the kidneys of damaged mice; a large amount of active oxygen or active nitrogen in the renal canaliculus